1988
DOI: 10.1002/ajh.2830290117
|View full text |Cite
|
Sign up to set email alerts
|

Atypical haplotypes linked to the βs gene in Africa are likely to be the product of recombination

Abstract: We report here the haplotypes of 10 MstII-defined SS patients and a S/beta o thalassemia from the Central African Republic, exhibiting 7 different atypical haplotypes that are different from the typical Bantu haplotype that characterize over 93% of the beta s bearing chromosomes in that region of Africa. Of the seven atypical haplotypes, six can be easily interpreted as the result of recombination around the "hot spot" 5' of the beta gene, between a typical Bantu haplotype and other haplotypes available in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3
3

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 6 publications
4
20
3
3
Order By: Relevance
“…Benin is the most frequent with a frequency of 0.479, followed by Bantu (0.406), Senegal (0.031), and Saudi Arabia/Indian (0.021). The Bantu A2 and Bantu A7 atypical haplotypes described by Srinivas et al (1988) were observed with a frequency of 0.042 and 0.021, respectively. No Cameroon haplotypes were identified in this study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Benin is the most frequent with a frequency of 0.479, followed by Bantu (0.406), Senegal (0.031), and Saudi Arabia/Indian (0.021). The Bantu A2 and Bantu A7 atypical haplotypes described by Srinivas et al (1988) were observed with a frequency of 0.042 and 0.021, respectively. No Cameroon haplotypes were identified in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The frequencies of the two atypical haplotypes, Bantu A2 (4.2%) and Bantu A7 (2.1%), are some of the highest reported in American populations. This observation can be interpreted as resulting from of recombinatorial events involving the Bantu typical haplotype and the 5' regions from various haplotypes present in normal individuals as described by Srinivas et al (1988). In an admixed population such as the Venezuelan, there are more probabilities of observing these events.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases from Brazil represent mutations or recombinations involving the Bantu ␤ S -gene; in two previous studies [7,8], the structure of the atypical haplotypes revealed recombinations only of the Bantu haplotype. This is probably due to the fact that all those studies were carried out in regions where the Bantu haplotype predominates: Angola, Mozambique, and Brazil [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Little attention has been paid to these atypical haplotypes. One study refers to them as variations of the Bantu haplotype whereas other reports consider them as the product of recombination of Bantu haplotypes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the atypical haplotype Bantu A2 (20%) is the highest reported in American populations so far. This haplotype may arise as the result of recombination events between the 5' regions of the Bantu typical haplotype and other haplotypes present in b A chromosomes (Srinivas et al, 1988). However, this figure may be overestimated due to the small number of chromosomes analyzed.…”
Section: Discussionmentioning
confidence: 91%